Aprendizagem da função gerencial em bancos - Hito, Silvia Cristina (2011)
This research had the overall goal understanding how the learning process of managerial function occurs in banks. To achieve the overall aim, two specific goals were defined. First specific goal: compare managers function by identification and descrition of tasks/responsabilities of relationship/accounts managers from a public and a private bank. Second specific goal: identify, describe and compare the learning process of relationship/accounts managers from a public and a private bank. This study contributes to an understudied field in an area of great economic importance in Brazil, which are banks. Were found only four related research, but with different audiences, and none of them brought comparison of learning process in institutions from different origins. Theories and concepts that have underpinned this research were: learning at work and the theory of formal and informal learning. The choice of learning at work theory occurred because of it taking into consideration factors beyond the intrinsic learning of employees and environmental conditions, a critical point in the search organizations, particularly in banks, the site of this study. The research was a descriptive and exploratory, it adopted a qualitative perspective and developed according to the assumptions of the basic or generic qualitative study , so that the objective was reached. The basic strategy for data collection was done through interviews, and the informal observations of the workplace and consultation on the banks websites were used to support analysis. The creation of codes in principle deductive and subsequently analytical contributed to the organization, analysis and creation of hierarchical categories and subcategories. In both of banks it was verified that manager s tasks and responsibilities had few similarity with manager s function defined by Fayol (1994). The survey revealed that participants learned human and technical skills through various forms of informal learning. In both banks the technical tasks learning occurred through consultation support tools and colleagues/expert, in addition to the error, but there was difference in the hierarchy of them. In relation to the learning of human skills, the observation and managers guidance, and reflection were specially quoted. It was perceived that the stressful environment of agencies make it difficult to learn or improve it. The stress in Public Bank is more related to lack of time due to various tasks and pressure to achieve goals, and the type of management, and in the Private Bank is more connected to the pressure to achieve goals. Were also identified in the two banks some influential factors in learning, how: to like, to need and believe in the task. And there were some indications of different forms of learning as age result. Requiring more detailed research on this issue.